Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

What substitution should be used to rewrite 6(x 5)2 5(x 5) – 4 = 0 as a quadratic equation? u = (x 5) u = (x – 5) u = (x 5)2 u = (x – 5)2

Sagot :

The substitution that should be used to rewrite 6(x+5)^2 + 5(x+5) - 4 = 0 is u = x + 5

Quadratic equations

These are equations that has a leading degree of 2. Given the expression

6(x+5)^2 + 5(x+5) - 4 = 0

In order to simplify this equation, we will replace the reoccuring term by a variable.

From the equation we can see that (x+5) is occuring the most. Let u = x + 5 so that:

6u^2 - 5u - 4 = 0

Hence the substitution that should be used to rewrite 6(x+5)^2 + 5(x+5) - 4 = 0 is u = x + 5

Learn more on quadratic equation here: https://brainly.com/question/1214333

#SPJ4